MARKETING MIX FACTORS AFFECTING CAR USERS’ DECISION PROCESS TOWARDS CAR SLIDE SERVICE SELECTION IN BANGKOK - Puengrattana, Natthanicha; Changchenkit, Chuenjit (Journal of MCU Nakhondhat, 2022)
The objectives of this research article were 1) to study the level of marketing mix factors affecting car users’ decision process towards car slide service selection in Bangkok, 2) to study the affecting car users’ decision process towards car slide service selection in Bangkok, and 3) influence of affecting car users’ decision process towards car slide service selection in Bangkok. It is exploratory research and descriptive research. It was used to collect 400 data from car users on slide-car service selection in Bangkok District. Described: percentage, mean, standard deviation, and the inferential statistics used to test the hypothesis was multiple regression analysis. The results of the study revealed that the level of marketing mix factors affecting car users’ decision towards car slide service selection in the Bangkok district as a whole was at a high level. It was found that the first place was the location and the service, followed by the products and the price. The last aspect is the personal aspect and decision-making process for using the slide car service selection in the Bangkok district. Overall, it’s at a high level. When considering each aspect, it was found that the first was the perception of the need, followed by the decision to use the service. and searching for information. The final ranking is Alternative evaluation. The results of analysis using multiple regression analysis showed the relationship between marketing mix factors affecting the decision to use the slide car service selection in the Bangkok district. There was a statistically significant at 0.01 level and a linear relationship at the 0.05 level.